(untitled) (Scientific journal of the Fergana State University, 2026)
The Aktau Botanical-Geographical Region is considered one of the least-studied areas of Uzbekistan. Analysis of the collected herbarium specimens indicates that research was conducted in the region up until 1970, after which it gradually declined. These studies have demonstrated that information about the region’s flora is insufficient and highlighted the need for further research using modern methods. The number of historical herbarium specimens amounts to 1728, belonging to 53 families, 185 genera, and 462 species.